Biology - Raven, Peter H. (McGraw-Hill Higher Education, 2005)
BIOLOGY is an authoritative majors textbook with evolution as a unifying theme. In revising the text, McGraw-Hill has consulted extensively with previous users, noted experts and professors in the field. It is distinguished from other texts by its strong emphasis on natural selection and the evolutionary process that explains biodiversity.